Finland's Famous Education System Unvarnished Insights into Finnish Schooling - Thrupp, Martin; Seppänen, Piia; Kauko, Jaakko; Kosunen, Sonja (Springer Nature Singapore : Imprint: Springer, 2023)
This open access book provides academic insights and serves as a platform for research-informed discussion about education in Finland. Bringing together the work of more than 50 authors across 28 chapters, it presents a major collection of critical views of the Finnish education system and topics that cohere around social justice concerns. It questions rhetoric, myths, and commonly held assumptions surrounding Finnish schooling. This book draws on the fields of sociology of education, education policy, urban studies, and policy sociology. It makes use of a range of research methodologies including ethnography, case study and discourse analysis, and references the work of relevant theorists, including Bourdieu and Foucault. This book aims to provide a critical, updated and astute analysis of the strengths and challenges of the Finnish education system. .